Automated Mango Irrigation System Using Soil Water Potential Measurement Technique - Kakham, Phumiphat (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2025)
This study presents an automated mango irrigation system based on soil water potential measurements. Soil water potential, which reflects the plant’s water uptake needs, was measured using tensiometers. The irrigation system was developed on an Arduino-based platform and integrated with two tensiometers and a solar-powered water pump. The firmware was programmed to initiate watering when natural light exceeded 20,000 lux and the soil water potential fell below -25 kPa at 1/4 of the root zone depth and -10 kPa at 3/4 of the root zone depth. Watering ended when soil water potential at 1/4 of the root zone depth exceeds -25 kPa. The system was tested in a farmer's mango orchard in Pak Nam Subdistrict, Bang Khla District, Chachoengsao Province. This irrigation system was tested in a farmer's mango orchard in Pak Nam Subdistrict, Bang Khla District, Chachoengsao Province, between December 20, 2021, and January 11, 2022. Results showed that the system automatically irrigated the mango tress approximately 8 times per day between 8.00 AM and 4.00 PM, corresponding to 6.20% of operational hours. The soil water potential with 1/4 of the root zone depth was maintained between -10 and -30 kPa, with an average value of 53.16%. This range represents an optimal moisture level, allowing plant roots to efficiently absorb water from the soil.